2003
DOI: 10.1111/j.1744-7348.2003.tb00262.x
|View full text |Cite
|
Sign up to set email alerts
|

The host range of Tobacco streak virus in India and transmission by thrips

Abstract: Summary Tobacco streak virus (TSV) recently caused an epidemic in peanut (= groundnut, Arachis hypogaea) crops in Andhra Pradesh, India. In the epidemic area TSV occurred in many widely distributed weeds of which Parthenium hysterophorus probably plays a major role in its spread by thrips. Three thrips species, Megalurothrips usitatus, Frankliniella schultzei and Scirtothrips dorsalis were vectors in the presence of infected pollen. Of crop species, Helianthus annuus (sunflower) and Tagetes patula (marigold) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
57
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(57 citation statements)
references
References 7 publications
0
57
0
Order By: Relevance
“…This type of results was supported by Bhaskara Reddy et al (2012) who raised the polyclonal antibody against the TSV and showed positive reaction for sample collected from natural infection of Hibiscus cannabinus in DAC-ELISA. Prasad Rao et al (2003) also proved the detection of a new strain SB-10 of TSV from potato through DAC-ELISA. In our study virus preparation has reacted with the antiserum specific to TSV, which was produced approximately 29 kDa protein in western blot assay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This type of results was supported by Bhaskara Reddy et al (2012) who raised the polyclonal antibody against the TSV and showed positive reaction for sample collected from natural infection of Hibiscus cannabinus in DAC-ELISA. Prasad Rao et al (2003) also proved the detection of a new strain SB-10 of TSV from potato through DAC-ELISA. In our study virus preparation has reacted with the antiserum specific to TSV, which was produced approximately 29 kDa protein in western blot assay.…”
Section: Discussionmentioning
confidence: 99%
“…TSV can be transmitted mechanically, but the transmission of TSV commonly occurs through different species of thrips viz., Megalurothrips usitatus, Frankliniella schultzei, Scirtothrips dorsalis, Thrips palmi and Thrips tabaci under field conditions (Jagtap et al, 2012) Alternative host plants have been suspected to harbour TSV which have contributed in its transmission. The virus causes asymptomatic infections in several common weed species, including Parthenium hysterophorus, Ageratum conyzoides and Corchorus trilocularis, whose pollen is a major source of TSV and these plants, also harbour thrips (Prasada Rao et al, 2003;Shukla et al, 2005). Though the occurrence of TSV has been reported from many hosts in India, only limited reports are available on the biological and molecular characterization of these isolates and their exact identification remains unaddressed in soybean.…”
Section: Introductionmentioning
confidence: 99%
“…dorsalis is also mentioned as a vector of the chilli leaf curl virus (CLCV) and tobacco streak virus (TSV) (Prasada Rao et al, 2003).…”
Section: 5mentioning
confidence: 99%
“…In India, TSV was first reported on sunflower (Bhat et al, 2002) and subsequently reported in several agricultural and horticultural crops (Prasada Rao et al, 2003;Vemana & Jain, 2010;Sivaprasad et al, 2010). TSV is pollen-borne and is easily spread by thrips under field conditions (Prasada Rao et al, 2003).…”
mentioning
confidence: 99%
“…TSV is pollen-borne and is easily spread by thrips under field conditions (Prasada Rao et al, 2003). TSV infection in jasmineis widespread in A.P.…”
mentioning
confidence: 99%